Kids with special needs : information and activities to promote awareness and understanding / written by Veronica Getskow and Dee Konczal ; illustrated by Bev Armstrong. - Getskow, Veronica (Learning Works, 1996)
Summary, Presents both the myths and the facts about disabilities